Barrett's esophageal adenocarcinoma diagnosed by narrow‐band imaging magnifying endoscopy. (25th April 2013) - Takahashi, Akiko; Oyama, Tsuneo
Abstract : A 40‐year‐old man was referred to our hospital for detailed examination of a protuberant lesion in long‐segment Barrett's esophagus (LSBE). Under white light endoscopy (WLE) the lesion appeared as a protuberant lesion with a rough surface and was diagnosed as 0‐IIa‐type tumor suspected to be a well‐differentiated adenocarcinoma. A regular villous pattern was shown in the background mucosa of the LSBE by narrow‐band imaging (NBI) magnifying endoscopy (NBI‐ME). However, a slightly irregular villous pattern was observed on the lateral side of the main lesion. Therefore, a 0‐IIa‐type tumor was estimated to have a flatly lateral extension component (i.e. 0‐IIb spreading). The 0‐IIb spreading was unclear when using WLE, but could be diagnosed by NBI‐ME based on the surface pattern differences. Markings were placed outside the edge of the flatly lateral extension, and endoscopic submucosal dissection was carried out.The pathological diagnosis of the protuberant lesion with flatly lateral spreading was well‐differentiated adenocarcinoma. The macroscopic type was 0‐IIa+IIb, 45 × 43 mm in size. The invasion depth was T1a (deep muscularis mucosae). Lymphatic and venous invasions were negative; horizontal and vertical margins were negative. In conclusion, NBI‐ME was useful for the diagnosis of the flatly lateral extension of this 0‐IIa+IIb esophageal adenocarcinoma in Barrett's esophagus. Further investigations with many cases are necessary.